Volatility co-movement of Asean-5 equity markets - Lau, Evan; Oh, Swee-Ling; Puah, Chin-Hong; Shazali Abu, Mansor (EBSCO, 2010)
Economic cross-linkages and the increased co-movement of asset prices across international markets are important outcomes as the result of globalization. Hereby, the nature of international stock markets and the extent to which the 1997-1998 East Asian turmoil had affected the market relationship of five countries of Association of Southeast Asian Nations (ASEAN-5) remain as probing questions. Using an array of econometrics analysis upon the stock price volatility series, we found partial market integration for the pre-crisis; whereas in the post-crisis, complete integration prevails. Hence, the financial meltdown in 1997 is said to be a contagion led crisis as markets integrate well off after the crisis than prior to it. Nonetheless, long run portfolio asset diversification benefits across the ASEAN-5 basin are reduced as markets are integrated in both the pre- and post-crisis. As such, the formation of the ASEAN Investment Area (AIA- 1998) parallel with the establishment of a developed ASEAN Index-Financial Times Stock Exchange (FTSE) regional index is viable to foster deeper regional market convergence.